Comparison of the 2010 and 2020 ecosystem structures in Xihu Harbor based on the Ecopath model. (1st November 2021) - He, Cong-Ying; Mao, Shuo-Qian; Yan, Xiao-Jun; Meng, Kuan-Hong; Hu, Dai-Fu
Abstract: The Ecopath with Ecosim modeling software was used to construct a Ecopath model for two time periods based on the 2010 and 2020 Xihu Harbor marine ecological environmental survey data. Changes in the Xihu Harbor ecosystem structure over the 10 years were determined, and management recommendations were proposed. The model includes 20 functional groups such as detritus, phytoplankton, Spartina alterniflora, zooplankton, benthic mollusks, Sciaenidae, other planktivorous fish, other piscivorous fish, and sea birds, and cover the Xihu Harbor ecosystem energy flow pathways. The analysis results showed that the types and biomass of important organisms changed during the 10 years; the total resources drastically decreased, fishery resources decreased by almost half, benthic organisms and plankton increased, and the mean ecotrophic efficiency decreased slightly (from 0.493 to 0.472). In 2010, the total energy flow from primary producers to each trophic level was 1406 t/km 2 ·a, and the total energy flow from detritus to each trophic level was 1559 t/km 2 ·a. In 2020, the total energy flow from primary producers to each trophic level was 2628 t/km 2 ·a, and the total energy flow from detritus to each trophic level was 2751 t/km 2 ·a. The energy input from primary producers and detritus in the Xihu Harbor ecosystem increased significantly. This was because macroalgae cultivation and expansion of S. alterniflora increased primary productivity as well as the expansion of the scale of mariculture, which increased detritus biomass and supported a high amount of energy flow through the system. The main reasons for changes in the Xihu Harbor ecosystem structure were S. alterniflora invasion, changes in aquaculture structure, and the decline in fishery resources. We propose targeted marine management measures, including using local salt marsh plants to replace S. alterniflora to maintain high primary productivity, continuing optimization to improve mariculture structure, and strengthening the seedling release of marine organisms. Graphical abstract: Image 1